Trichoderma koningiopsis 2OI2A1M: produção de enzimas do complexo hemicelulolítico e aplicação na sacarificação do bagaço de cevada - Kerber, Caroline Marlene da Cruz (2020)
Filamentous fungi are excellent sources of industrial enzymes because of their high production and secretion capacity to the extracellular environment. Xylanases, cellulases, pectinases, amylases and invertases are examples of hydrolases, which have wide application in different industrial sectors. There are several uses of these enzymes, notably the food and beverage, animal feed, textile and pulp and paper industries. In addition, there is growing interest in the use of agricultural waste as a raw material in the production of bioethanol. Trichoderma fungi are well known and exploited for producing multiple enzymes for polysaccharide degradation, such as cellulose and hemicellulose. The Trichoderma koningiopsis species is reported as cosmopolitan but is still little explored in the biotechnological field. Thus, this study aimed to investigate the ability of T. koningiopsis 2OI2A1M fungus, previously isolated from the Paraná Atlantic Forest Biome, to produce enzymes that act on the depolymerization of lignocellulosic biomass found in agroindustrial byproducts, aiming at an application of these enzymes in saccharification of barley bagasse. The production of xylanase by T. koningiopsis 2OI2A1M fungus using different agroindustrial residues showed that barley bagasse provided higher enzymatic activity (83.91 U mL-1). Additionally, it has been found that kraft paper is capable of inducing xylanase production (51.93 U mL-1). Among the extracellular β-xylosidases and β- glucosidases, sorghum biomass and carboxymethylcellulose were the best inducer with 22.63 and 36.40 U mL-1, respectively. The crude extract xylanase of T. koningiopsis 2OI2A1M exhibited maximum activity pH and temperature at 5.0 and 60 °C, respectively. The xylanase activity remained totally preserved for 6 days of incubation at 4 °C, in the pH range 3.5-7.0, however, its activity was affected when incubated for more than 60 min at temperatures above 40 °C. The production of fermentable sugars from the enzymatic saccharification of barley bagasse, the in natura condition, yielded a higher concentration of glucose (5.9%), total reducing sugars (13.3%), and xylose (2.6%) after 48 h. The comparative analysis of the morphological structure of the barley bagasse by scanning electron microscopy demonstrated that the simultaneous action of T. koningiopsis 2OI2A1M enzymes does not require previous structural modifications in the barley bagasse for effectiveness in the saccharification process. Thus, the fungus T. koningiopsis 2OI2A1M has potential to produce enzymes that act on the depolymerization of lignocellulosic biomass and barley bagasse is an attractive candidate for a sustainable alternative for the production of fermentable sugars, a primary focus in the production of secondgeneration fuels such as bioethanol.